Analyzing the Roles of Trust, Commitment, and Brand Image in the Bottled Water Industry - Siregar, Farhan Helmi Alvidoansyah; Anggraito, Muhammad; Libing, Pamela Ayu Otto; Silalahi, Sarah Achsanti (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2024)
Corporate Social Responsibility (CSR) plays a significant role in marketing activities within the Fast-Moving Consumer Goods sector. The impact of customers' perception of CSR on their purchase intentions is influenced by intermediaries and specific situations. This research aims to explore methods for bottled drinking watercompanies to shape and influence customer behavior towards consistent support. By harnessing CSR perception, building trust, fostering commitment, and enhancing brand image, these companies can achieve this goal effectively. To achieve this objective, the researchers conducted an online survey among a sample of customers in Indonesia. The collected data was analyzed using linear regression analysis, which allowed for a thorough examination of the relationships between variables. CSR perception has a positive effect on trust, commitment, and brand image. Brand image and commitment have a positive effect on purchase intention, while trust does not.